Implementasi Metode Teams Games Tournament Untuk Meningkatkan Capaian Belajar Siswa Materi Surah Al Bayyinah di MDTA Baabussalam - Bahiyah, Qonita Elviana; Arza, Medi Yulison; Fakhri, Muhammad Umar; Yusron, Muhammad; Gusti Banafsa, Nabilla Cintana (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
Abstract Within the context of Islamic education, educators assume a pivotal role in fostering an engaging and culturally suitable learning environment for students. However, the implementation of Quranic education frequently encounters obstacles, particularly in achieving optimal learning outcomes. Focus of this study is to enhance the learning outcomes of fifth-grade at MDTA Baabussalam in relation to the surah Al-Bayyinah. The approach employed is the TGT, with a snakes and ladders game serving as the medium. The impetus for this study stems from the underperformance of students in comprehending the contents of the surah. The methodology employed is Classroom Action Research, comprising two cycles, each encompassing planning, implementation, observation, and reflection stages. The assessment instruments consist of 10 multiple-choice and 5 essay. The analysis employed a combination of qualitative and quantitative techniques to comprehensively describe the results. The findings indicated a substantial enhancement in students' learning outcomes, with a transition from 10% in the pre-cycle to 50% in Cycle I and an escalation to 95% in Cycle II. These finding serves to substantiate the efficacy of the TGT method in enhancing students' comprehension of the Qur'anic text, particularly Surah Al-Bayyinah. Keywords: Student Learning Outcomes, Surah Al Bayyinah, Teams Games Tournament Abstrak Dalam konteks pendidikan Islam, pendidik memegang peran sentral dalam menghadirkan lingkungan belajar yang menarik dan sesuai dengan budaya bagi siswa. Namun, implementasi pendidikan Al-Quran seringkali menghadapi hambatan, terutama dalam mencapai capaian belajar yang optimal. Fokus penelitian ini adalah untuk meningkatkan capaian belajar siswa kelas lima di MDTA Baabussalam terkait surah Al-Bayyinah. Pendekatan yang digunakan adalah TGT, dengan permainan ular tangga sebagai media. Dorongan untuk penelitian ini berasal dari kinerja siswa yang kurang memuaskan dalam memahami isi surah Al-Bayyinah. Metode yang digunakan adalah Penelitian Tindakan Kelas, yang terdiri dari 2 siklus, masing-masing meliputi tahap perencanaan, implementasi, observasi, dan refleksi. Alat penilaian terdiri dari 10 pertanyaan PG dan 5 pertanyaan esai. Analisis menggunakan kombinasi teknik kualitatif dan kuantitatif untuk menggambarkan capaian secara komprehensif. Hasil penelitian menunjukkan peningkatan yang besar dalam capaian nilai siswa, dengan persentase yang meningkat dari 10% pada pra-siklus menjadi 50% pada Siklus I dan meningkat menjadi 95% pada Siklus II. Temuan ini menunjukkan bahwasanya pendekatan TGT, menggunakan bentuk permainan ular tangga, dapat meningkatkan pemahaman siswa terhadap Surah Al Bayyinah. Keywords: Capaian Pembelajaran Siswa, Surah Al Bayyinah, Teams Games Tournament